Slit2-Mediated Metabolic Reprogramming in Bone Marrow-Derived Macrophages Enhances Antitumor Immunity - Kaul, Kirti; Benej, Martin; Mishra, Sanjay; Ahirwar, Dinesh K.; Yadav, Marshleen; Stanford, Kristin I.; Jacob, Naduparambil K.; Denko, Nicholas C.; Ganju, Ramesh K. (Frontiers in Immunology, 2021)
Slit2 exerts antitumor effects in various cancers; however, the underlying mechanism, especially its role in regulating the immune, especially in the bone marrow niche, system is still unknown. Elucidating the behavior of macrophages in tumor progression can potentially improve immunotherapy. Using a spontaneous mammary tumor virus promoter-polyoma middle T antigen (PyMT) breast cancer mouse model, we observed that Slit2 increased the abundance of antitumor M1 macrophage in the bone marrow upon differentiation in vitro. Moreover, myeloablated PyMT mice injected with Slit2-treated bone marrow allografts showed a marked reduction in tumor growth, with enhanced recruitment of M1 macrophage in their tumor stroma. Mechanistic studies revealed that Slit2 significantly enhanced glycolysis and reduced fatty acid oxidation in bone marrow-derived macrophages (BMDMs). Slit2 treatment also altered mitochondrial respiration metabolites in macrophages isolated from healthy human blood that were treated with plasma from breast cancer patients. Overall, this study, for the first time, shows that Slit2 increases BMDM polarization toward antitumor phenotype by modulating immune-metabolism. Furthermore, this study provides evidence that soluble Slit2 could be developed as novel therapeutic strategy to enhance antitumor immune response.